Aligning Leader Behaviors With Innovation Requirements Improves Performance: An Experimental Study - Gerlach, Friederike; Heinigk, Katharina; Rosing, Kathrin; Zacher, Hannes (Frontiers in Psychology, 2020)
In this experiment, the effect of the alignment of leader behaviors with innovation requirements was investigated. A sample of N = 245 students participated in a laboratory experiment. Participants had to address either creativity or implementation requirements within a task and received a leadership manipulation in a video message. Results showed that the alignment of leader behaviors with innovation requirements led to improved performance. These findings contribute to the literature by addressing the specific requirements within the innovation process and by showing that aligning leader behaviors with these requirements contributes to performance in the innovation process.